Application of a decision-making tool for ranking wellness tourism destinations - Paula Lopes, Ana (2022)
Abstract: One of the tourism industry’s segments with the strongest growth rates today is health tourism. Health tourism includes two subgroups: medical tourism (traveling outside one’s country of residence for the purpose of receiving medical care, such as surgery and health services) and wellness tourism (travel to specific locations for health promotion in a preventive way). The economic strength and sustainable growth of nations can both benefit from health tourism. This study applies a methodology to quantify the potential of Portuguese wellness tourism (thermal spas in Northern Portugal) using a multi-criteria decision making (MCDM) tool, namely the preference ranking organization method for enrichment evaluations (PROMETHEE) and geometrical analysis for interactive aid (GAIA), to achieve a robust evaluation and ranking the alternatives. Therefore, in this study, the aim is to rank ten thermal spas in Northern Portugal in terms of fifteen indicators, mostly related to digital services, containing the tourism data obtained between 2020 and 2022. The suggested approach offers trustworthy and reliable outcomes for any qualitative or quantitative criteria to assess thermal spas, which is crucial for consumers, businesses, and even governments. The results showed that PROMETHEE and GAIA can be implemented as an effective method in wellness tourism destinations evaluation.